The effects of birth order on neonatal outcomes in early-preterm, late-preterm and term twin infants*. (17th June 2020) - Kim, Soo Hyun; Kim, Yoo-Min; Sung, Ji-Hee; Choi, Suk-Joo; Oh, Soo-Young; Roh, Cheong-Rae
Abstract: Objectives: Birth order is one of the main factors that influences the neonatal outcome of twins. However, there is little prior data regarding the effect of birth order under different clinical circumstances. This study investigates the effect of birth order on the neonatal outcomes of twins delivered during early-preterm, late-preterm and term gestations according to chorionicity, delivery mode and indication for delivery. Methods: This is a retrospective cohort study of women with twin pregnancies delivered at 24–40 weeks of gestation between 1995 and 2014. We excluded twin pregnancies with the following complications: twin-to-twin transfusion syndrome, monoamnionic twins, delayed interval delivery and fetal death, chromosomal anomalies or major congenital malformation in one or more of the twins. The neonatal outcomes, including death, admission to neonatal intensive care unit (NICU), mechanical ventilator support, and respiratory distress syndrome (RDS) was compared between the first and second twin born at early-preterm (24–33 weeks of gestation), late-preterm (34–36 weeks of gestation) and term (≥37 weeks of gestation) gestations. These outcomes were further analyzed according to chorionicity, mode of delivery and indication for delivery by multivariable analysis (after adjusting for sex, presentation, and birth weight). Results: Among a total of 1, 614 women with twin pregnancies who met the selection criteria, 423, 674 and 517 women delivered at early-preterm, late-preterm and term gestation, respectively. Overall, the second-born twins were lighter and had higher rates of NICU admission, mechanical ventilator support, and RDS than did first-born twins. Second twins born at early-preterm gestation had higher rates of RDS and mechanical ventilator support than did first twins. Second twins born at late-preterm gestation had higher rates of NICU admission and mechanical ventilator support than did first twins. Second twins born at term gestation also had a higher NICU admission rate than did first twins. However, in the multivariable analysis of the subgroups, the rates of NICU admission, mechanical ventilator support and RDS were not significantly different between most twin pairs. However, there were several significant differences. There was a higher risk of RDS in the second twins in the early-preterm premature rupture of membranes (PROM) subgroup, and a higher risk of mechanical ventilator support in the late-preterm PROM subgroup. Low birth weight was the only significant factor independently associated with a higher risk of adverse neonatal outcome in the second twins compared with the first twins in all subgroups. Conclusions: Second twins born at early-preterm, late-preterm and term were at higher risk of adverse neonatal outcome than were their respective first twins. However, this finding was mainly represented lower birth weight of the second twin. Still, second twins delivered due to early-preterm and late-preterm PROM had a higher risk of RDS and mechanical ventilator support, respectively, than did the first twin after adjusting for birth weight.